Soil bio-cementation using a new one-phase low-pH injection method - Cheng, L.; Shahin, Mohamed; Chu, J. (2018)
Soil bio-cementation via microbially induced carbonate precipitation (MICP) has been extensively studied as a promising alternative technique to traditional chemical cementing agents for ground improvement. The multiple-phase injection methods are currently well adopted for MICP treatment, but it is rather complex and requires excessive number of injections. This paper presents a novel one-phase injection method using low-pH all-in-one biocement solution (i.e. a mixture of bacterial culture, urea, and CaCl2). The key feature of this method is that the lag period of the bio-cementation process can be controlled by adjusting the biomass concentration, urease activity, and pH. This process prevents the clogging of bio-flocs formation and thus allows the biocement solution to be well distributed inside the soil matrix before bio-cementation takes effect, allowing a relatively uniform MICP treatment to be achieved. Furthermore, the ammonia gas release would be reduced by more than 90%, which represents a significant improvement in the environmental friendliness of the technology. The new one-phase method is also effective in terms of the mechanical property of MICP-treated soil; an unconfined compressive strength of 2.5 MPa was achieved for sand after six treatments.